Energetic criterion in general elastic-plastic fracture mechanics - Dan, Bui Huu (Vietnam Journal of Mechanics, 1993)
From the analyzing the equation of energy balance for cracked bodies during the crack growth the energetic criterion is formulated for general elastic-plastic fracture mechanics. The numerical procedure should be realized by using the slip model of polycrystalline plasticity and the experimental data.